Degradation of a REBCO conductor due to an axial tensile stress under edgewise bending: a major stress mode of deterioration in a high field REBCO coil's performance. (25th May 2017) - Kajita, K; Takao, T; Maeda, H; Yanagisawa, Y
Abstract: The influence of an axial tensile stress under edgewise bending on the current transport property of a REBCO-coated conductor is described from the viewpoint of it being one of the major stress modes of degradation in a high field REBCO coil's performance due to electromagnetic forces. A new type of a tensile experiment for the combination of an axial tensile stress, edgewise bending and flatwise bending on a REBCO conductor demonstrates that the combined stress increases tensile strain at the outer edge of the conductor and generates mechanical cracks in the superconducting layer, which causes an earlier degradation than a pure tensile stress. This combined stress mode can cause degradation of a high field REBCO coil's performance below an operating hoop stress and countermeasures need to be developed.